Spatial and temporal aspects of demographic and migration processes in the regions of Ukraine - Провотар, Наталія Іванівна; Сторожик Д.М. (Київський національний університет імені Тараса Шевченка, 2024)
The article is dedicated to examining the spatial aspects of demographic and migration processes across the regions of Ukraine. The study covers the period from 1991 to 2021. Ukraine is experiencing a demographic crisis, characterized by natural population decline, reduced birth rates, increased mortality among working-age men, deterioration in the gender and age structure of the population, and population aging. The analysis of the dynamics of natural population movement indicators and migration balance highlights specific features of demographic and migration processes in various regions of Ukraine. The study also includes analysis for both urban and rural areas. Regions were grouped based on the characteristics of their demographic and migration processes, with groups identified for different years within the study period, followed by a comparative analysis. The components of the demographic and migration crises in the regions are outlined. It was found that during Ukraine's demographic crisis, demographic and migration processes acquired new characteristics, significantly impacting population distribution and the socio-economic development of the regions, posing challenges for future development. Consequently, the importance of the country’s demographic and migration policies has grown even more crucial.

Стаття присвячена дослідженню просторових аспектів демографічних та міграційних процесів в регіонах України. Для дослідження було обрано період 1991-2021 рр. За результатами аналізу динаміки показників природного руху населення та сальдо міграцій визначено особливості демографічних і міграційних процесів у регіонах України. Здійснено групування регіонів за особливостями демографічних і міграційних процесів та окреслено складові демографічної і міграційної криз в регіонах. Виявлено, що за час демографічної кризи в Україні, демографічні та міграційні процеси набули нових рис, суттєво вплинули на розселення населення та соціальноекономічний розвиток регіонів, стали одним із викликів для подальшого розвитку. У зв’язку з цим ще важливішого значення набуває демографічна та міграційна політика держави.
Просторові та часові аспекти демографічних і міграційних процесів у регіонах України
Keywords: природний приріст населення; демографічні процеси; міграції; міграційні процеси; регіони; Україна; natural population growth; demographic processes; migration; migration processes; regions; Ukraine